Peranan Pendidikan Agama Kristen Bagi Pemuda Kristen - James Mangaronda (Sekolah Tinggi Agama Kristen Lentera Bangsa Manado, 2022)
Christian Religious Education for Christian youth is a learning process from a Christian perspective to instill Christian values and cultivate youth minds with the word of God through the guidance of the Holy Spirit with various learning experiences, so that young people experience progressive spiritual growth that is getting deeper and deeper in knowing God through devotion to God, to the church, to society, to the nation and state. With the role of Christian religious education for youth, every Christian youth will realize that they are young people who have a responsibility to take part in bulding the nation and answer every problem faced by the church, the environment and the nation. Christian youth are the next generation and the strength of the church and nation therefore youth must be provided with adequate Christian religious education so that the identity of a Christian youth will be formed according to the word of God where they can be role models. So, the role of Christian religious education for Christian youth is to bring Christian youth into the fellowship of faith with the Lord Jesus in whom they are counted as His congregation who acknowledge and glorify Him at all times and in every place, become instruments in His hands and become salt and light for the church, environment, nation and state.